FGFR Family Members Protein Expression as Prognostic Markers in Oral Cavity and Oropharyngeal Squamous Cell Carcinoma - Koole, Koos (Mol Diagn Ther, 2016)
INTRODUCTION: Fibroblast growth factor receptor family member proteins (FGFR1–4) have been identified as promising novel therapeutic targets and prognostic markers in a wide spectrum of solid tumors. The present study investigates the expression and prognostic value of four FGFR family member proteins in a large multicenter oral cavity squamous cell carcinoma (OCSCC) and oropharyngeal squamous cell carcinoma (OPSCC) cohort. METHODS: Protein expression of FGFR1–4 was determined by immunohistochemistry on tissue microarrays containing 951 formalin-fixed paraffin embedded OCSCC and OPSCC tissues from the University Medical Center Utrecht and University Medical Center Groningen. Protein expression was correlated to overall survival using Cox regression models, and bootstrapping was performed as internal validation. RESULTS: FGFR proteins were highly expressed in 39–64 % of OCSCC and 63–79 % of OPSCC. Seventy-three percent (299/412) of OCSCC and 85 % (305/357) of OPSCC highly co-expressed two or more FGFR family member proteins. FGFR1 protein was more frequently highly expressed in human papillomavirus (HPV)-negative OPSCC than HPV-positive OPSCC (82 vs. 65 %; p = 0.008). Furthermore, protein expression of FGFR family members was not related to overall survival in OCSCC or OPSCC (p > 0.05). CONCLUSION: FGFR family members are frequently highly expressed in OCSCC and OPSCC. These FGFR family member proteins are therefore potential targets for novel therapies that are urgently required to improve survival of OCSCC and OPSCC patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40291-016-0204-5) contains supplementary material, which is available to authorized users.